2001
DOI: 10.1097/00001721-200101000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the fibrinolytic enzyme system on prognosis and survival associated with non-small cell lung carcinoma

Abstract: Comprehensive studies of fibrinolysis in non-small cell lung carcinoma have been limited, and assignment of patients to high/low prognosis groups based on arbitrary cut-offs utilizing fibrinolytic measurements is unstandardized. This study was performed in 166 patients to examine the effects of cut-off values determined in three ways. Model 1 assigned patients to one of three equal groups (low, medium, high) based on fibrinolytic measurements made at diagnosis, Model 2 divided patients into low/high groups usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 11 publications
2
33
0
1
Order By: Relevance
“…We focused on DD, a unique marker of coagulation and fibrinolytic activation. Our previous experience 16,17 and other studies 12,15,39 indicated that DD was the most useful variable. The weakness of the current study is that it does not provide any completely new evidence (approximately 7 of the 10 years encompassed by the current report, and 629 of 826 patients [76%] were included in the 2 previous publications).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…We focused on DD, a unique marker of coagulation and fibrinolytic activation. Our previous experience 16,17 and other studies 12,15,39 indicated that DD was the most useful variable. The weakness of the current study is that it does not provide any completely new evidence (approximately 7 of the 10 years encompassed by the current report, and 629 of 826 patients [76%] were included in the 2 previous publications).…”
Section: Discussionmentioning
confidence: 82%
“…32 As in many other human malignancies, [33][34][35][36][37][38] including lung carcinoma, DD might have prognostic significance. 12,15,39 In 1993, Seitz et al 12 reported that TAT and DD were significantly increased in patients with metastatic disease and that elevated TAT values at diagnosis might be prognostically significant. Taguchi et al 15 measured the plasma levels of DD in 70 lung carcinoma patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cancer patients, several studies have reported high plasma concentrations of procoagulant proteins and decreased concentrations of functionally attenuated anti-coagulant factors [23][24][25]. Low fibrinolytic function has been also reported to be an important cause of vascular thrombosis in cancer patients [17]. So far, increased circulating level of PAI-1 has been ascribed as the main causative factor of hypofibrinolysis in patients with malignancy including those with lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cells themselves may be the source of PAI-1 and PAI-2 [14,16]. The association of poor prognosis with circulating and tumor PAI-1 levels in patients with lung cancer illustrates the clinical relevance of fibrinolytic inhibitors in malignancy [17].…”
Section: Introductionmentioning
confidence: 99%